KONVERGENSI MEDIA DALAM PROGRAM “AFTER HOURS WITH HELMY YAHYA” DI INEWS - Irmawati Oktavianingtyas; Udi Rusadi (Universitas Tribhuwana Tungga Dewi, 2021)
After Hours with Helmy Yahya is a talk show program produced by Inews TV, under the auspices of the MNC Group. But unfortunately the program was terminated after airing for no more than 2 months. Convergence as a strategy for media companies to survive in the digital era has been applied to the program, but apparently this does not affect the success of the program. Therefore, the author wants to know the application of media convergence in the